The relative effect of parasites and social status on sperm traits in Arctic charr - Figenschou, Lars; Folstad, Ivar; Rudolfsen, Geir; Hanssen, Sveinn Are; Kortet, Raine; Skau, Philip; Killie, Jan Eirik; Oskam, Irma Caroline; Strand, Harald (Behavioral Ecology, 2013)
Sperm production and sperm swimming speed, which most likely affect fertilization under sperm competition, are modified by proximate mechanisms. In a comprehensive observational study of free-living and reproductively active Arctic charr (Salvelinus alpinus), we examined the possible modulating effects of male social status (including ornamental development), parasite intensities, and immunity on novel traits indicative of ejaculate quality (e.g., Adenosine triphosphate (ATP) in sperm cells, levels of immunoglobulins attached to sperm cells, and the degree of DNA fragmentation in sperm cells). A multiple regression model showed no relationship between DNA fragmentation in sperm cells and abdominal coloration of charr, suggesting that sperm of colorful males are not better protected against oxidative stress. We found, however, that males with traits indicative of high social status had low amounts of ATP in sperm cells and also sperm cells with low swimming speed. Sperm production, on the other hand, was strongly predicted by parasite intensities only and these associations were mainly positive. Our results suggest that the presence of parasites seems to stimulate sperm production similar to what is observed among males entering subordinate reproductive roles. Thus, if resistance toward parasites is influencing parasite intensities, resistance may also indirectly be important for the “choice” of reproductive role and in turn investment in primary sex traits. Key words: Arctic charr, immunity, parasite intensity, sexual selection, social status, sperm quality. [Behav Ecol